Contamination of waterborne parasites at water treatment plants and a gravity-feed system : a highlight on water safety for urban and rural communities in Kuching, Sarawak - Ahmad Syatir, Tahar; Lesley Maurice, Bilung; Kasing, Apun; Reena Leeba, Richard; Hashimatul Fatma, Hashim; Elexson, Nillian; Lau, Seng; Yvonne Ai Lian, Lim (NAUN Publications, 2022)
Waterborne parasites, particularly Cryptosporidium and Giardia, are emerging pathogens implicating the safety level of drinking water globally. The aim of this study was to determine the distribution pattern of waterborne parasites in raw and treated water at urban and rural water treatment plants and untreated water from gravity-feed system in Kuching, Sarawak. This study focused on water treatment plants (four urban and two rural) and Bong rural community that utilise gravity-feed system in Kuching, Sarawak. A total of 69 raw and treated water samples were collected and processed before being used in detection of Cryptosporidium and Giardia using Aqua-Glo™ G/C Direct and 4′,6-diamidino-2-phenylindole stains, as well as other parasites that were detected using Lugol’s iodine staining. Parameters which were temperature, pH, turbidity, dissolved oxygen, total dissolved solids, conductivity, faecal coliform of the water as well as rainfall intensity were determined. Correlation of the parameters with distribution of the waterborne parasites was analysed. Out of 69 water samples collected across all localities, 25 samples were contaminated with waterborne parasites with varying waterborne parasite concentration in the water samples. The presence of waterborne parasites in the raw and treated water of water treatment plants in this study signifies public health threats do exist despite being conventionally treated. This study also highlights that the gravity-feed system which is commonly depended by rural communities in Malaysia may facilitate waterborne parasitic infections